Impact of Miniso Bangladesh's events activation and PR on their brand personality and subsequent growth - Chowdhury, Ahnaf Monzoor (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.